MASCULINO 58 AÑOS, DIABÉTICO E HIPERTENSO CON CUADRO SUBAGUDO DE CERVICALGIA, PARESTESIAS Y DEBILIDAD EN MIEMBROS SUPERIORES QUE EVOLUCIONA A TETRAPARESIA ESPÁSTICA - Avila Sánchez, Diego (2011)
A 58 years old male, with history of diabetesmellitus and hypertension whom presented to ourhospital with subacute neck pain and paresthesias of upper limbs, complicated later with cervicalcord syndrome. There was evidence of C6-C7 vertebral osteomyelitis and cervical instability.Debridement was performed, along with stabilization and repair of the cervical spine. Blood andbone cultures were negative and empirical therapy with parenteral vancomycin (4-week course) was started, followed by oral ciprofloxacin (4-weeks course). Clinical evolution was satisfactory.